Post-Antibiotic Gut Microbiota Recovery in the Rumen: Insights into Colonization Patterns, Population Density, and Diversity Dynamics - Md. Emran Hossain (International Journal of Antibiotics, 2025)
The post-antibiotic recovery of gut microbiota represents a critical area of research in understanding how microbial communities rebalance and re-establish homeostasis following antibiotic-induced disruptions. Antibiotics, while effective against infections, can cause substantial shifts in gut microbiota, leading to dysbiosis – a state of microbial imbalance that impairs gut health and functions. This recovery process involves multiple complex dynamics, including colonization patterns, population density, and the restoration of microbial diversity. The key factors influencing this recovery are microbial resilience, colonization dynamics, the role of keystone species, competition among microbes, and host-microbiota interactions. Therapeutic strategies, such as the use of probiotics, synbiotics, fecal microbiota transplantation, and alternative antimicrobial therapies, have been explored to aid in microbial recolonization and restore gut functionality. This study aims to comprehensively investigate the mechanisms underlying the post-antibiotic recovery of the gut microbiota. It focuses on understanding how microbial populations reorganize, the role of keystone species in rebuilding ecosystem stability, and the potential of various therapeutic approaches. Additionally, it examines how host factors, such as immune responses and dietary interventions, influence recovery. Insights into these processes will provide critical knowledge for developing strategies to promote healthy microbial communities, improve gut function, and mitigate the long-term impacts of antibiotic treatment on gut health.
Keywords: Antibiotic-induced dysbiosis; Gut microbiota; colonization dynamics; functional recovery; host-microbiota diversity; microbial resilience; post-antibiotic recovery